Performance expectations of professional sport teams and in-season head coach dismissals: Evidence from the English and French men's football first divisions - Yvon Rocaboy; Marek Pavlik (Economies, 2020)
The goals of this paper are first to identify why professional football clubs replace their head coach and, second, to investigate the effect of coach dismissal on team performance. To do that, we propose a new method for assessing the performance expectations of professional sport teams using Monte Carlo simulation. We apply our method to the English Premier league and the French Ligue 1 football teams over the 2015-2016 and 2016-2017 seasons. We find that coach dismissal is the result of a drop in the average expected performance compared with the performance expectations at the beginning of the season. We also show that dismissing a coach may enhance performance only if the team under-performed before the dismissal. There is no obstacle to using the same method for professional teams in other sports. The method is easily reproducible and does not require much information in order to be applied.
Keywords: 330; coach dismissal; Monte Carlo simulation; team performance; payrolls; expectations